Translation Procedures and Ideology of Two Different English Translation Versions of Surah Al-Fatihah: A Contrastive Analysis - RISYAH ADILIA (FACULTY OF HUMANITIES, 2019)
This research elaborates how surah al-Fatihah as the important surah in the Holy Qur‟an is translated into two different English translation versions by Saheeh International (2004) and Abdel Haleem (2004) with certain procedures and ideologies. Several theories which are contrastive analysis, the theory of English and Arabic sentence structures, the theory of translation procedures, and the theory of translation ideology are used to support this research. This study is conducted by applying qualitative method and case study as the research strategy. The data are the lexical and grammatical differences in the form of words, phrases, clauses, and sentences. In order to collect data from the sources, the two English translation versions of surah al-Fatihah by SI and AH are broken down into the translation of each ayah. Then, they are read critically to find the lexical and grammatical differences. Afterward, the data are analyzed using contrastive analysis and English sentence structure theory. Subsequently, the results of the contrastive analysis are interpreted to see the translation procedures applied by each translator by elaborating them using the theory of translation procedures and Arabic sentence structures. Then, the different procedures which are applied by both translators are compared to determine the translation ideologies. The results of the analysis show that SI and AH applied different translation ideologies, therefore, resulted in the application of different translation procedures which is reflected in the lexical and grammatical differences in the translations. The translation version by SI applied foreignization ideology and tends to be SLT-oriented while the translation version by AH applied domestication ideology and tends to be TLT-oriented.
reupload file repository 7 april 2026 izza/tofik
Keywords: Translation; Ideology; Surah Al-Fatihah